A new graphical method for heat exchanger network design involving phase changes - Yeo, Y. S. (Italian Association of Chemical Engineering - AIDIC, 2017)
Heat Exchanger Network Synthesis (HENS) plays a major role for effective energy integration in chemical process plants. In HENS, several hot and cold streams and utilities with specific inlet and desired outlet temperatures are involved. Stream Temperature versus Enthalpy Plot (STEP) is new graphical tool which can complement Composite Curves (CCs) and Grid Diagram (GD) by representing individual, as opposed to composite streams on temperature versus enthalpy diagram, and by allowing designers to perform targeting and network design simultaneously. Previous researches do not consider the effect of phase changes in the hot and cold streams and assume constant specific heat capacity, Cp along process streams. The aim of this study is to propose a new graphical method for HENS targeting and network design involving phase changes. Using an illustrative example, STEP procedure is proposed for the determination of minimum utility targets with the minimum number of heat exchangers. Results of the analysis using the modified STEP is compared with those obtained using Composite Curves. It is found that the modified STEP provides more accurate and realistic results and allows the selection of different types of heat exchangers.